Attachment‐informed therapy for adults: Towards a unifying perspective on practice. (14th July 2015) - Berry, Katherine; Danquah, Adam
Abstract : Purpose: We aimed to provide an integrated overview of the key goals and strategies of an attachment‐informed psychotherapy by summarizing the literature describing the clinical implications of attachment theory for psychological therapy for adults. Method: We carried out a narrative thematic review of 58 texts from a diverse range of therapeutic schools, until we agreed that we had reached a saturation of themes. Results: We identified six key themes: Changing internal working models; the therapeutic relationship and creating a secure base; formulating and processing relationship experiences; countertransference; separation, termination and boundary issues; and working with different attachment styles or patterns. We discuss empirical evidence in relation to each theme and highlight areas for research. Conclusions: Attachment theory provides a useful framework to inform psychological therapy with adults, but there is a pressing need for further research to empirically demonstrate the 'added value' of an attachment perspective. Practitioner points: Attachment theory should be used to inform individual psychological therapy in adulthood. From the outset of their careers, therapists should receive training and supervision to enhance their awareness of their own and their clients' attachment experiences and how these play out during therapy. There is a need for greater empirical research to investigate whether the degree to which therapists formulate and meet clients' attachment needs influences outcomes.